RELASI ANTARA KEMAMPUAN PEMAHAMAN MATEMATIK SISWA SMP DENGAN METODE PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE - Levia Hasvi Ambarwati; Iwan Setiawan; Padillah Akbar; Muhammad Afrilianto (Departement of Mathematics Education, 2019)
The problem that becomes background of this research, the abilitity of mathematical understanding of students is still lowThe purposes of this research are to know the influences of the use of active learning model type Everyone is a Teacher Here on raising the abilitity of mathematical understanding of students and to know students response of mathematics learning by using mathematics learning model. The method that is used in this research is Experimental, with research design Non-Equivalent Control Group Design. The research is done in SMP N 1 IBUN. The population in this research is all of students of class VII-C as experiment class and class VII-B students as control class that is choosed randomly. And the instrument that is used is mathematical understanding test, observation sheet of students learning activity and questionnaire. In this research obtained qualitative data and quantitative data. Based on analysis of the result of the abilitity of mathematical understanding test concluded that active learning model type Everyone is a Teacher Here has positive effect on abilitity of mathematical understanding of students in mathematics learning. While based on analysis of observation sheet and questionnaire concluded that there is raising students learning activity in mathematics learning by using active learning model type Everyone is a Teacher, and the students give positive response on mathematics learning by using active learning model type Everyone is a Teacher Here